Capturing the value of vaccination within health technology assessment and health economics: Literature review and novel conceptual framework. Issue 30 (26th June 2022) - Beck, Ekkehard; Biundo, Eliana; Devlin, Nancy; Doherty, T. Mark; Garcia-Ruiz, Antonio J.; Postma, Maarten; Sheikh, Shazia; Smela, Beata; Toumi, Mondher; Wasem, Jurgen; Nolan, Terry; Salisbury, David
Graphical abstract: Highlights: Vaccination produces important individual health gains and broad societal benefits. Current vaccine economic evaluation (EE) approach often excludes broader benefits. A novel Value of Vaccination framework was developed with unique concepts for EE. Dimensions include conventional payer and societal, and novel societal concepts. Conventional and novel societal gain concepts need to be appraised in EE. Abstract: Background: Vaccination provides significant health gains to individuals and society and can potentially improve health equity, healthcare systems and national economies. Policy decisions, however, are rarely informed by comprehensive economic evaluations (EE) including vaccination's wide-ranging value. The objective of this analysis was to focus on health technology assessment systems to identify relevant value concepts in order to improve current EE of non-pandemic vaccines. Methods: Following a literature review, a novel Value of Vaccination (VoV) framework was developed with experts in vaccine EE from developed countries with established health technology assessment systems. Results: Forty-four studies presenting value frameworks or concepts applicable to vaccination were included. Eighteen unique value concepts relevant to EE were identified and defined. These were categorised within the VoV framework using three dimensions, moving from a narrow payer perspective to a more expansive and societal perspective. The dimensions were: (I) conventional payer perspective concepts (e.g., health gains in vaccinees, direct medical costs); (II) conventional societal perspective concepts (e.g., indirect health/economic gains to caregivers/households, productivity in vaccinees); and (III) novel societal concepts (e.g., financial risk protection, peace of mind, societal health gains, healthcare systems security, political stability, social equity and macroeconomic gains). While good quality evidence and methods are available to support concepts in Dimensions I and II, further work is needed to generate the required evidence for vaccination impact on Dimension III concepts. Conclusions: The devastating effect on nations of the COVID-19 pandemic has helped to highlight the potential far-reaching benefits that many vaccination programmes can offer. This VoV framework is particularly relevant to policy decisions considering EE, and the potential future expansion of non-pandemic vaccination value considerations. The framework helps to understand and compare current value considerations across countries and payer versus societal perspectives. It provides decision-makers with a transparent and logical path to broaden consideration of VoV in EE.